2011
DOI: 10.1161/hypertensionaha.110.168245
|View full text |Cite
|
Sign up to set email alerts
|

Role of Asymmetrical Dimethylarginine in Inflammation-Induced Endothelial Dysfunction in Human Atherosclerosis

Abstract: Abstract-We explored the role of asymmetrical dimethylarginine (ADMA) as a cause of endothelial dysfunction induced by systemic inflammation. In vitro data suggest that ADMA bioavailability is regulated by proinflammatory stimuli, but it is unclear whether ADMA is a link between inflammation and endothelial dysfunction in humans. In study 1 we recruited 351 patients with coronary artery disease (CAD) and 87 healthy controls. In study 2 we recruited 69 CAD, 69 healthy, and 10 patients with rheumatoid arthritis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 25 publications
(15 reference statements)
0
53
1
2
Order By: Relevance
“…Importantly, in our study, CRT did not affect ADMA concentrations also indicating that NO generation via endothelial NO synthase activation was likely to be unaffected. In one previous study, high ADMA concentrations tended to predict poor responses to endothelial NO synthase activation by FMD 26. A further caveat concerning the current findings is that evaluation of changes in platelets and blood may not be fully representative of changes within the myocardium.…”
Section: Discussioncontrasting
confidence: 76%
“…Importantly, in our study, CRT did not affect ADMA concentrations also indicating that NO generation via endothelial NO synthase activation was likely to be unaffected. In one previous study, high ADMA concentrations tended to predict poor responses to endothelial NO synthase activation by FMD 26. A further caveat concerning the current findings is that evaluation of changes in platelets and blood may not be fully representative of changes within the myocardium.…”
Section: Discussioncontrasting
confidence: 76%
“…In patients undergoing coronary bypass surgery, it was observed that ADMA levels were correlated with elevated NOS-derived generation of ROS 33 . Furthermore, it has been shown that ROS upregulate ADMA synthesis and protein arginine N-methyltransferase expression 34 . In cell culture studies, it has been shown that pro-oxidant and pro-inflammatory stimulants inhibit dimethylarginine dimethylaminohydrolase (DDAH) activity 35 .…”
Section: Discussionmentioning
confidence: 99%
“…ADMA has been suspected for the development of inflammatory response and proposed that ADMA may be a link between inflammation and endothelial dysfunction in humans. Antoniades et al also suggested that systemic, low-grade inflammation leads to increased ADMA [28]. A strong positive correlation between CRP, fibrinogen and plasma ADMA levels has been shown in a study [29].…”
Section: Discussionmentioning
confidence: 85%